122 DIAMOND 2.0: Updating a Pioneering Digital Platform for Study Team Workforce Development - Brenda Eakin; Elias Samuels; Vicki L. Ellingrod (Journal of Clinical and Translational Science, 2023)
OBJECTIVES/GOALS: There is a critical need to provide quality training for study teams. Materials need to be flexible and available at the learner’s preferred time and format. DIAMOND was developed to provide nimble education offerings that respond to the changing landscape of clinical and translational research. METHODS/STUDY POPULATION: In 2018 four CTSA institutions (the University of Michigan, the Ohio State University, Rochester University, and Tufts University) collaborated to launch the DIAMOND portal. Developed as a CTSA-wide web-based platform, DIAMOND allows members of clinical and translational research teams to widely share and access training and education resources. In 2022 a MICHR-led update of DIAMOND used principles of user centered design to improve the platform. New features include updated search functions to quickly find and sort training materials, tagging training materials to the characteristics of a translational scientist, and development of user controlled customized playlists. RESULTS/ANTICIPATED RESULTS: DIAMOND currently includes 217 training resources developed by 30 CTSA hubs and private industry. The platform has over 600 page views per day from users across the U.S. and internationally. DIAMOND includes an easy-to-use form to upload new materials to the platform. Contributors are asked to include key words and select competency domains and characteristics of a translational scientist that apply to their materials. Other new features include tagging materials to streamline and improve search results, the ability to sort materials by competency domain or characteristics of a translational scientist, and the ability for users to create and share customized, personalized playlists. DISCUSSION/SIGNIFICANCE: DIAMOND is an important tool to support workforce development for study teams. Updates to the flexible digital platform meet the needs and preferences of adult learners and busy health professionals. Lessons learned from the design process and future plans for the platform will be explored.